EFEKTIFITAS PENINGKATAN PENGETAHUAN REMAJA PUTRI TENTANG PENCEGAHAN KEPUTIHAN DENGAN MEDIA LEAFLET DAN E-BOOK - Nengsih, Novida; Suib, Suib (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2024)
Background : Vaginal discharge is a disorder that often occurs in adolescence, in the form of a vaginal condition where fluid resembles pus. Vaginal discharge tends to have a foul odor, is greenish in color and is sometimes accompanied by itching. If not treated properly, vaginal discharge can disrupt the function of the female reproductive organs which can cause infertility. Healthy behavior must be carried out by teenagers to avoid reproductive health problems. Lack of knowledge is an inhibiting factor for healthy behavior. Method : This quantitative research uses a quasi experimental pretest posttest group design. The research divided into two treatment groups, namely the vaginal discharge prevention counseling group for adolescent girls who were given leaflets and the vaginal discharge prevention counseling group for adolescent girls who were given an E Book. This research was conducted at SMK N 4 Muaro Jambi Regency. The population of this study were all young women at SMK N 4 Muaro Jambi Regency, totaling 148 respondents. Samples were taken using stratified proportional random sampling. The analysis test uses the paired t test. Result : The results of the analysis of the influence of leaflet health education on knowledge of vaginal discharge prevention in young women obtained p value = 0.000. The test results of the effect of E-Book health education regarding the prevention of vaginal discharge obtained p value = 0.000. This p value of 0.000 shows that there is an influence of knowledge about preventing vaginal discharge in young women using both leaflets and e-books. The results of the effectiveness test, the average knowledge of young women after being given health education with leaflets was 15.64. The average knowledge value of young women after being given health education using E Book media is 16.23. The results of the analysis test obtained p value = 0.005. Conclusion : So it was concluded that there was an increase in the knowledge of young women regarding the prevention of vaginal discharge and it was stated that the E-book media was more effective in increasing the knowledge of young women regarding the prevention of vaginal discharge.